Kinetics, mechanism and density functional theory calculations on base hydrolysis of α-amino acid esters catalyzed by [Pd(AEMP)(H2O)2]2+ (AEMP = 2-(2-aminoethyl)-1-methylpyrrolidine) - Shoukry, Mohamed M.; Shehata, Mohamed R.; Ragab, Mona S.; Ćorćić, Dušan; Puchta, Ralph; van Eldik, Rudi (Reaction Kinetics Mechanisms and Catalysis, 2020)
Abstract: Pd(AEMP)Cl2 (AEMP = 2-(2-aminoethyl)-1-methylpyrrolidine) was synthesized and characterized by spectral and thermal measurements.[Pd(AEMP)(H2O)2]2+ reacts with amino acid esters (L) to form mixed ligand [Pd(AEMP)L]2+ complexes. The kinetics of the base hydrolysis of [Pd(AEMP)L]2+ was studied by a pH-stat technique and the corresponding rate constants are reported. The coordinated glycine methyl ester is hydrolyzed efficiently, whereas the coordinated methionine- and histidine- methyl esters undergo hydrolysis with a much lower catalytic activity. The catalytic effect is controlled by the mode of coordination of the ester to the Pd(II) complex. Possible mechanisms for these reactions are considered. Activation parameters were determined experimentally for the hydrolysis of the coordinated glycine methyl ester. DFT calculations (B3LYP/def2svp) were applied to gain further insight into the possible mechanism of the base hydrolysis of the amino acid esters. The calculations are discussed in reference to the reported experimental data. Graphic abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-02-25
Keywords: 2-(2-Aminoethyl)-1-methylpyrrolidine; Amino acid ester; Catalytic hydrolysis; DFT calculations; Pd(II); pH-stat technique